THE INFLUENCE OF MINIMUM INVESTMENT CAPITAL, RISK PERCEPTION OF STUDENTS INVESTMENT IN INDONESIA CAPITAL MARKET - Ardiana, Titin Eka; Sugianto, La Ode; Chamidah, Siti (International Journal of Economics, Business and Accounting Research (IJEBAR), 2020)
This study aims to assess the minimum investment capital to start investing, and minimize the risk of loss and business instinct to analyze what effects are good to buy and of course it will be profitable in investing in the capital market. The approach used in this research is quantitative explanative research. In this study, there are two kinds of variables used, namely the dependent variable and the independent variable. The dependent variable used for this study is student investment interest in the capital market, while the independent variable used in this study consists of minimum investment capital (X1), and risk perception (X2). The data collection technique in this study is to use primary data, namely a questionnaire (questionnaire). The analytical method used in this study is to use multiple linear regression analysis using calculations through SPSS version 20. The results show that there is a positive and significant effect of minimal investment capital and risk perception on student investment interest simultaneously at the Faculty of Economics, University of Muhammadiyah Ponorogo. The contribution of these two variables contributed 44.3% and the remaining 55.7% was influenced by other variables not examined in the study. Keywords: Minimum Investment Capital, Risk Perception, and Investment Interest